2020
DOI: 10.1097/fbp.0000000000000609
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1 receptor agonist, exendin-4, reduces reinstatement of heroin-seeking behavior in rats

Abstract: Opioid use disorder (OUD) causes the death of nearly 130 Americans daily. It is evident that new avenues for treatment are needed. To this end, studies have reported that 'satiety' agents such as the glucagon-like peptide-1 receptor (GLP-1R) agonist, exendin-4 (Ex-4), decreases responding for addictive drugs such as cocaine, nicotine, alcohol, and oxycodone, but no work has been done with heroin. In this study, we used a reward devaluation model in which rats avoid ingesting a saccharin solution that predicts … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 62 publications
(92 reference statements)
1
26
1
Order By: Relevance
“…The most studied GLP‐1R agonist in the field of addiction has been Exendin‐4 (Ex‐4), which has been observed to reduce motivated behaviours associated with amphetamine, cocaine, nicotine, alcohol and oxycodone 16–21 . In our hands, treatment with Ex‐4 significantly reduced both cue‐induced heroin seeking and drug‐induced reinstatement of heroin seeking in rats 22 . That said, while Ex‐4 has been shown to be effective in reducing drug‐associated behaviours in rats, its short half‐life requires it to be administered at least twice a day in humans.…”
Section: Introductionmentioning
confidence: 67%
“…The most studied GLP‐1R agonist in the field of addiction has been Exendin‐4 (Ex‐4), which has been observed to reduce motivated behaviours associated with amphetamine, cocaine, nicotine, alcohol and oxycodone 16–21 . In our hands, treatment with Ex‐4 significantly reduced both cue‐induced heroin seeking and drug‐induced reinstatement of heroin seeking in rats 22 . That said, while Ex‐4 has been shown to be effective in reducing drug‐associated behaviours in rats, its short half‐life requires it to be administered at least twice a day in humans.…”
Section: Introductionmentioning
confidence: 67%
“…The discrepant results in the self‐administration paradigm may indicate species differences between rats and mice. Indeed, another rat study reported that exenatide reduced responding for cues previously associated with heroin injections in a reinstatement procedure of operant behaviour (Douton et al, 2021). Treatment with the selective DPP‐4 inhibitor linagliptin was also reported to reduce morphine‐conditioned place preference and facilitate extinction of the morphine preference in rats (Łupina et al, 2020).…”
Section: Role Of Glp‐1 In Substance Use Disordermentioning
confidence: 99%
“…Mechanisms involving some form of satiation would be consistent with the known effects of GLP‐1 system stimulation on the regulation of nutrient intake. However, several studies have reported that GLP‐1 receptor stimulation can suppress drug‐conditioned behaviours, in both classical conditioning (CPP procedures) and operant conditioning (drug seeking using reinstatement procedures), that is, tests during which the drug is unavailable (Douton et al, 2021; Egecioglu, Steensland, et al, 2013; Egecioglu, Engel, & Jerlhag, 2013a, 2013b; Graham et al, 2013; Harasta et al, 2015; Hernandez et al, 2018, 2019, 2020; Shirazi et al, 2013; Sirohi et al, 2016; Vallöf et al, 2016; Vallöf, Kalafateli, et al, 2019; Vallöf, Vestlund, et al, 2019). This would suggest that GLP‐1 receptor stimulation also modulates mechanisms underlying drug and alcohol ‘seeking’ or ‘wanting’, and not only intake and satiation.…”
Section: Possible Mechanisms Of Actionmentioning
confidence: 99%
“…However, GLP-1R expression in other brain regions, such as the extended amygdala and PVN ( Ghosal et al, 2013 ), may also play a role in reduction of alcohol intake in preclinical models via modulation of stress-reinstatement pathways, although this has not been directly tested and findings on GLP-1R activation on anxiety-like behaviors have been mixed. Additional evidence suggests that GLP-1R agonist therapies may also be effective in reducing opioid intake and seeking in preclinical models ( Douton et al, 2021a , b ). Overall, NTS GLP-1 neuron function in the context of AUD and stress could be a line of research parallel to the effects of NTS NE and stress on alcohol mediated behaviors.…”
Section: Glucagon-like Peptidementioning
confidence: 99%